Hat trick - Morgan, Alex (Alexandra Patricia), 1989- (Morgan, Alex (Alexandra Patricia), 1989- Kicks., 2015)
With the playoffs over, Devin and her seventh-grade friends decide to try out for a soccer travel team, but friendships are threatened because not everyone makes it on to the tough, competitive team, and in the mean time the girls are faced with a crisis--budget cuts threaten to eliminate the soccer program at the elementary school Devin's little sister attends.